2021
DOI: 10.1002/ece3.8142
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptive responses of rosette‐type macrophyte Vallisneria natans juveniles to varying water depths: The role of leaf trait plasticity

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Contrary to our expectations, not all traits of the pond‐dwelling individuals responded to both abiotic and biotic variables. Three resource acquisition traits (height, SLA, and internode length) and one resource conservation trait (specific internode mass) were influenced by abiotic or biotic variables alone, although they are known to usually respond to both variable types (Pilon & Santamaría, 2002; Fu et al., 2013; Gao et al., 2021). However, all other trait variations (i.e., the LDMC, maximum root length, and specific root mass) responded to biotic and abiotic variables as predicted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to our expectations, not all traits of the pond‐dwelling individuals responded to both abiotic and biotic variables. Three resource acquisition traits (height, SLA, and internode length) and one resource conservation trait (specific internode mass) were influenced by abiotic or biotic variables alone, although they are known to usually respond to both variable types (Pilon & Santamaría, 2002; Fu et al., 2013; Gao et al., 2021). However, all other trait variations (i.e., the LDMC, maximum root length, and specific root mass) responded to biotic and abiotic variables as predicted.…”
Section: Discussionmentioning
confidence: 99%
“…ITV would allow a better resistance to filters (Jung et al., 2010; Violle et al., 2012) through adaptation (genetic variability) and/or phenotypic plasticity (Byars et al., 2007; Ghalambor et al., 2007; Albert et al., 2011). In aquatic plant communities, the high investment of macrophyte species in clonal growth suggests that resistance to filters mainly relies on plastic responses (Pilon & Santamaría, 2002; Wolfer & Straile, 2004; De Wilde et al., 2014; Li et al., 2019; Gao et al., 2021; Han et al., 2021). Most plant morphological traits are key for coping with environmental filters (see, e.g., Lavorel & Garnier, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redundancy analysis (RDA) was used to map the effects of environmental factors (pH, SWC, P, SOM, N, WA, WR, aspect, slope, mean elevation, and convex) among the four forest succession on the measured soil bacterial and fungal communities using the "vegan" package (Gao et al, 2021). Hellinger transformation was performed before RDA linear ordering of response variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Many studies have suggested that water depth is the most important factor for vegetation recovery (Wang et al, 2017;Li et al, 2017;Zhou et al, 2017;Gao et al, 2021). Another group of scholars supports that clear water is the foremost requirement for macrophytes to germinate and grow (Sondergaard et al, 2007;Mikulyuk et al, 2011;Su et al, 2019).…”
Section: Introductionmentioning
confidence: 99%